Effects of Condom Use, Anal Bleeding, and Group Sex on the Risk of HIV Infection in Men Who Have Sex: A Meta-Analysis - La Karman Gojali; Dinda Nabila Silva Diba; Jihan Nabilla; Bhisma Murti; Elsa Tursina (Masters Program in Public Health, 2024)
Background: Sexual transmission of HIV among men who have sex with men (MSM) continues to increase. There are several factors that affect the occurrence of HIV infection in Male Sex Addiction. In this study, we will discuss three factors, namely condom use, anal bleeding and sex group ownership. This study aims to analyze and estimate the strength of the relationship between the incidence of HIV infection and condom use, anal bleeding, and sex group ownership.Subjects and Method: A systematic review and meta-analysis study was conducted using the PICO model. Population: male sex male. Intervention: not using condoms, anal bleeding after sex, and having sex groups. Comparison: using a condom, no anal bleeding after sex, and no sex group. Outcome: HIV infection. The basic data used includes Google Scholar, Proquest, Scopus, PubMed, Zendy, ScienceDirect, BMC, Elsivier, and Springer Link. The inclusion criteria are full-text articles with a cross-sectional study design using multivariate and attaching aOR values and published 1996-2023. The Data analysis using the Review Manager 5.3 application.Results: This meta-analysis was carried out on seven cross-sectional studies originating from China, Tanzania, and Brazil. Total sample size=13,188 people. The risk of HIV infection in men who have sex with men increased with the use of no condoms (aOR= 1.35; CI 95%= 1.10 to 1.65; p= 0.004), there was anal bleeding after sex (aOR= 1.89; CI 95%= 1.53 to 2.34; p<0.001), and group sex (aOR= 2.30; CI 95%= 1.62 to 3.25); p<0.001).Conclusion: The risk of HIV infection in men who have sex with men increases by not using condoms, having anal bleeding after sex, and having group sex.